2006
DOI: 10.3136/fstr.12.235
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Polyphenol Oxidase from Edible Yam (Dioscorea opposita Thunb.)

Abstract: Soluble polyphenol oxidase of edible yam (Dioscorea opposita Thunb.) was purified approximately ,*--fold with a recovery rate of +/ῌ by ammonium sulfate fractionation, ion exchange chromatography, hydrophobic chromatography and gel filtration using dopamine as a substrate. The purified enzyme appeared as a single band on native PAGE and SDS-PAGE. The molecular weight of the enzyme was estimated to be approximately .,kDa and ..kDa using gel filtration and SDS-PAGE, respectively. The purified enzyme quickly oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The purified enzyme was very similar to PPO from edible yam (Dioscorea opposita Thunb.) (Fujita et al, 2006) and to the banana (Musa sapientum) pulp PPO (Yang et al, 2000), but different to the PPO from white yam (D. rotundata), which quickly oxidised chlorogenic acid and catechol (Ikediobi & Obasuyi, 1982). The different substrate specificity between Dioscorea cayenensis-rotundata cv.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The purified enzyme was very similar to PPO from edible yam (Dioscorea opposita Thunb.) (Fujita et al, 2006) and to the banana (Musa sapientum) pulp PPO (Yang et al, 2000), but different to the PPO from white yam (D. rotundata), which quickly oxidised chlorogenic acid and catechol (Ikediobi & Obasuyi, 1982). The different substrate specificity between Dioscorea cayenensis-rotundata cv.…”
Section: Discussionmentioning
confidence: 97%
“…Guiwei) fruit (Sun et al, 2008) and another species of yam tuber (Anosike & Ayaebene, 1981;Ikediobi & Obasuyi, 1982). However, it differed from PPOs of Barbados cherry (Malpighia glabra) (Kumar & Mohan, 2008) and edible yam (Dioscorea opposita) (Fujita et al, 2006). The pH stability profile for the enzyme showed that 100% of the PPO Y activity was retained between pH 6.0 and 7.0.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[38,40,41] Figure 2 shows the effect of the pH value on PPO-catalysed quinone oxidation of the bisphenol derivatives at 40°C. The conversion % value at the reaction time of 5 h was used as the evaluation index for BPB, BPC, and BPZ.…”
Section: Ppo-catalysed Quinone Oxidationmentioning
confidence: 99%